Can wearable technology predict pain like pain predicts the weather? - Gleadhill, S. (Journal of Fitness Research, 2016)
Measuring risk factors of injury with technology may be possible with inertial sensors. The aim was to highlight inertial sensor capabilities, to propose future research interventions. Student`s T tests were completed for statistical comparisons of gyroscope angular rate of change, between deadlifts completed with a neutral spine posture and a flexed spine posture. It was concluded that inertial sensors can monitor anterior-posterior spine technique differences in resistance exercise. Therefore future research is needed to assess the capability of inertial sensor technology to measure parameters of human movement that reflect the risk of sustaining injuries.